Determination of Isometric Points in the Stifle of a Dog Using a 3D Model - Yair, Nadav; Yiapanis, Christos; Ben-Amotz, Ron; Meiner, Yaron; Shapiro, Amir; Milgram, Joshua (Veterinary and Comparative Orthopaedics and Traumatology, 2023)
Objective The aim of this study was to develop a three-dimensional (3D) model to identify the isometric component of the cranial cruciate ligament (CCL) in dogs.Methods A static 3D model of the specimen was generated from a computed tomography scan of the stifle of a dog and a kinematic model was generated from data collected, every 5 degrees from full extension (131 degrees) through 80 degrees of stifle flexion, from four sensors attached to the tibia. Kinematic data were superimposed on the static model by aligning the points of interest, which were defined for both models. This allowed the tibia to rotate and translate relative to the femur based on the kinematic data. The contours of the distal femur and proximal tibia were converted into point clouds and the distance between each point in the femoral point cloud and all the points in the tibial point cloud were measured at each of the 15 positions. The difference between the maximum and minimum distances for each pair of points was calculated, and when it was less than 0.2 mm, points were illustrated as two red dots connected by a line at their locations on the femur and tibia.Results A total of 3,681 pairs of isometric points were identified and were located at the origin and insertion of the CCL and on the lateral aspect of the stifle.Conclusion Isometric areas are present at the origin and insertion of the CCL and lateral aspect of the stifle. Better understanding of these locations may lead to refinements in techniques to replace the ruptured CCL.
Keywords: dog; stifle; biomechanical; isometric points